Balance Scorecard Implementation Challenges in Institution of Higher Learning: Overview of Prior Studies - Anuforo, Peter U.; Ayoup, Hazeline; Saidu, Nasiru (American International Journal of Social Science Research, 2018)
The incessant decline in the performance of Malaysian public institution of higher learning since 2007 to date has brought to fore the question of its performance management process. Studies have shown that performance management is a general phenomenon in the institution of higher learning worldwide. The implementation issues of Balance scorecard (BSC) is more pronounced in the non-profit outfit and governmental organizations (NPGOs) compared to the profit-oriented outfit. Reasons being that the BSC was originally developed and (or) meant for the profit-oriented outfit and not exactly the other way round. The purpose of this paper is to provide insight into the issues of performance management in the institution of higher learning and specifically regarding the implementation issues of BSC encountered among Malaysia public institution of higher learning. This study provides a review of previous literature on the BSC implementation issues. Several implementation issues identified from the literatures are strategy misalignment, strategy communication issues, manager’s acceptance/employees buy-in, the issue of clarity of vision, mission, strategy, and outcome, and strategy map implementation issues. Findings revealed that the implementation issues of the BSC among Malaysia public institution actually helps to unravel the pitfalls of BSC project and provides a roadmap show that can improve and sustain effective performance management. The implication of this study is aimed at providing the means by which the Malaysian public institution of higher learning can identify the issues inherent in BSC implementation or strategy implementation and the way forward.